Major CIED Infections Significantly Lower with Use of Antibacterial Envelope - Rizzo, Toni (MD Conference Express, 2013)
Infections associated with cardiovascular implantable electronic devices (CIEDs) cause substantial morbidity and mortality. The AIGISRx antibacterial envelope (ABE) for prophylaxis of CIED infections was approved by the Food and Drug Administration in 2008 for use with perioperative IV antibiotics. The AIGISRx Envelope for Prevention of Infection Following Replacement With an Implantable Cardioverter-Defibrillator (ICD) [CITADEL; NCT01043861] or Cardiac Resynchronization Therapy Device (CRT) [CENTURION; NCT01043705] trials prospectively evaluated the effectiveness of the ABE in patients implanted with a non-de novo single- or dual-chamber ICD (CITADEL) or non-de novo CRT (CENTURION) devices.